Silicone Breast Implants as a Model System for Understanding Polymer Permeation in Soft Materials In Vivo - D. Bouyer; H. Mutlu; C. Charmette; E. Randrianaridera; Z. Adaidi; R. Hedna; L. Pieuchot; I. Pluvy; K. Anselme; N. Couturier; J. P. Mericq; A. Ponche; et al. (Advanced Healthcare Materials, 2026)
ABSTRACT Silicone breast implants have long been associated with the gradual release of low molecular weight siloxanes from the inner gel through the implant membrane into the periprosthetic biological environment, a phenomenon commonly referred to as “gel bleed.” Despite more than five decades of investigation spanning polymer science, transport theory, and biomedical research, the physicochemical mechanisms underlying silicone permeation remain conceptually fragmented. Here, we revisit silicone permeation by examining how molecular transport arises from the intrinsic interplay between polymer architecture, thermodynamic partitioning, and diffusional mobility within crosslinked networks. We further analyze the key determinants of permeation, including implant aging, barrier‐layer technologies, and interaction with the periprosthetic tissue environment. We further discuss how dynamic bio‐interfaces influence bidirectional transport and bioaccumulation in vivo. Beyond their implications for implant performance, these observations provide broader conceptual insights into mass transport in soft materials, highlighting general principles relevant to elastomers, hydrogels, and drug‐delivery systems. By integrating material structure, transport physics and host interactions, this review establishes a mechanistic viewpoint on polymer permeation in vivo and offers design considerations for next‐generation soft implantable biomaterials.